Humanitarian Intervention And Just War Theory: Case of Kosovo - Sellita (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2023)
The Kosovo crisis occurred from February 1998 until 1999 in the former Yugoslavia. This conflict started when ethnic Albanians opposed ethnic Serbians and the Yugoslav government in Kosovo. International reactions to the upsurge of the Kosovo crisis have been prompt because of its urgency. Ethnic cleansing became good considering the international response. The intervention was carried out by NATO in the Kosovo crisis. The intervention by NATO raises speculation about humanitarian intervention during the crisis and whether it is justifiable or vice versa. According to the principle of Just War Theory, human intervention can be justified by logical explanations. NATO interventions in the Kosovo crisis are the appropriate instance to describe these situations by Just War Theory.